Ongoing circulation of emerging tick-borne viruses in Poland, Eastern Europe - Koray Ergunay; Gocha Golubiani; Giorgi Kirkitadze; Drew D. Reinbold-Wasson; Brian P. Bourke; Cody A. Phelps; Adam Kotorashvili; Nato Kotaria; Christine E. Hulseberg; Tamar Chunashvili; Andrew Sydenstricker; Anano Shubashishvili; et al. (PLoS ONE, 2025)
In order to investigate previously reported expansion of tick-borne pathogenic viruses in Eastern Europe, we conducted this study using pooled ticks collected from various locations in Poland, utilizing Sequence Independent Single Primer Amplification (SISPA) and metagenomic sequencing. We processed 575 Dermacentor reticulatus and Ixodes ricinus ticks and generated 280 virus assemblies in 20 pools. Viruses representing 28 species or strains classified in 12 families or higher taxonomic ranks were observed. We identified four tick-borne human pathogens including Alongshan virus (ALSV), Tacheng tick virus 1 (TcTV-1), Tacheng tick virus 2 (TcTV-2) and Nuomin virus (NUMV), in 55% of the pools, comprising 19.2% of the assemblies. We detected ALSV in I. ricinus ticks, with virus genome segments in complete or near-complete forms, comprising the initial reporting of ALSV from Poland. Further analyses revealed phylogenomic clustering with ALSV strains from Europe and lack of recombination signals among virus genomes. TcTV-1 was detected in 35% of the pools comprising D. reticulatus and I. ricinus ticks, implicating I. ricinus in TcTV-1 transmission for the first time. Maximum likelihood analyses on TcTV-1 and TcTV-2 genome segments indicated separate clustering patterns suggesting geographically-segregated clades. Evidence for NUMV or a closely-related chuvirus in I. ricinus ticks was further noted. In conclusion, we identified persistence of previously-documented tick-borne pathogens in Poland as well as additional viruses such as ALSV. Assessment of temporal and spatial patterns for virus circulation and diagnostic assays for these agents is needed. The distribution and public health impact of these pathogens throughout Europe require further investigation.